IFITs: Emerging Roles as Key Anti-Viral Proteins - Vladimer, Gregory I.; Górna, Maria W.; Superti-Furga, Giulio (Frontiers in Immunology, 2014)
Interferon-induced protein with tetratricopeptide repeats (IFITs) are a family of proteins which are strongly induced downstream of type I interferon (IFN) signaling. The molecular mechanism of IFIT anti-viral activity has been studied in some detail, including the recently discovered direct binding of viral nucleic acid, the binding to viral and host proteins, and the possible involvement in anti-viral immune signal propagation. The unique structures of some members of the IFIT family have been solved to reveal an internal pocket for non-sequence-specific, but conformation- and modification-specific, nucleic acid binding. This review will focus on recent discoveries which link IFITs to the anti-viral response, intrinsic to the innate immune system.